Multimodality treatment of oligometastatic anal squamous cell carcinoma: A case series and literature review. Issue 4 (12th January 2019) - Sclafani, Francesco; Hesselberg, Gina; Thompson, Stephen R.; Truskett, Philip; Haghighi, Koroush; Rao, Sheela; Goldstein, David
Abstract : Background and Objectives: There is limited evidence to guide the management of patients with oligometastatic anal squamous cell carcinoma (SCC). We aimed to address this question by reporting the outcome of SCC patients who were treated with organ‐directed therapies at two large cancer centers. Methods: Patients with advanced anal SCC who were treated with surgery, stereotactic radiotherapy, or radiofrequency ablation (RFA) with a curative intent from 2008 to 2017 were retrospectively identified from the institutional electronic patient records. Results: Eight patients with liver or lung metastases met the study inclusion criteria. Seven were treated with surgery while one received RFA and radiotherapy. Median progression‐free survival was 5 months (range, 4‐39). Three patients underwent repeat organ‐directed treatment upon failure of the initial surgery with no evidence of further recurrent disease at the last follow‐up. Median overall survival from the time of the first organ‐directed therapy was 31 months (range, 11‐96) with two out of eight patients being alive and disease‐free at 5 years. Conclusions: Our study confirms that consideration should be given to the adoption of a multidisciplinary treatment approach in carefully selected, oligometastatic anal SCC patients as organ‐directed therapies may offer the chance of achieving a relatively long disease control.